Controle da vibração de transporte vertical considerando a aplicação de amortecedores magneto-reológicos - Santos, Leandro Camargo Claro dos (2017)
This work aims to present a study of a vertical transportation of high performance system, as vibration levels with its displacement at higher speeds are uncomfortable to passengers. To the reduction of these vibrations, it is proposed the using of magnetorheological dampers (MR) controlled by the electric current applied to the coil of the damper, with the objective of reducing acceleration or horizontal displacement of the elevator. They were proposed two control logic to the control of damper’s electric current: a control considering Fuzzy logic aiming to reduce the horizontal displacement, and an Optimum Linear Quadratic Regulator control (LQR) in order to reduce the acceleration level of elevator vibration and its horizontal displacement. Both strategies determine the electric current to be applied in the damper coil. Numerical results presented in the work showed the controls were efficient to reduce the horizontal displacement, however only LQR control was efficient in reduce the acceleration levels.